2005
DOI: 10.1021/ja042264h
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Thermotropic Liquid Crystal Dendrimers

Abstract: The synthesis and characterization of two families of ionic liquid crystal dendrimers consisting of the ammonium salts of the commercially available poly(amidoamine) (G = 0-5) and poly(propylene imine) (G = 1-5) dendrimers and three long-chain carboxylic acids are reported. The liquid crystalline behavior was investigated by means of differential scanning calorimetry, polarizing light optical microscopy, and X-ray diffractometry. The thermal stability of the ionic materials was further studied by NMR. Most of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
114
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(119 citation statements)
references
References 42 publications
5
114
0
Order By: Relevance
“…We employ a numerical solution of the SCFT equations (eq [13][14][15][16][17][18][19] to evaluate the canonical ensemble free energies for various candidate inhomogeneous phases in their unit cells. Initial field configurations are seeded in order to produce a unit cell of a given mesophase, and the modified diffusion equation (eq 9) is solved pseudospectrally with an operator splitting scheme.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We employ a numerical solution of the SCFT equations (eq [13][14][15][16][17][18][19] to evaluate the canonical ensemble free energies for various candidate inhomogeneous phases in their unit cells. Initial field configurations are seeded in order to produce a unit cell of a given mesophase, and the modified diffusion equation (eq 9) is solved pseudospectrally with an operator splitting scheme.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…38 Using the calculated propagators, the volume fractions and single-molecule partition functions are evaluated. The W A , W B , W C , and P fields are subsequently relaxed using various convergence schemes 26,39,40 in order to satisfy the remaining SCFT equations, (eqs [16][17][18][19]. We also minimize the free energy density with respect to the volume and shape of the periodic simulation box with a variable cell shape method.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…26 In the case of ionic complexation, various polyelectrolyte architectures such as linear and hyperbranched polymers as well as dendrimers have been explored as macromolecular templates and complexed with ionic mesogenes such as hydrocarbon-based surfactants and rigid rods. [27][28][29][30] Biopolyelectrolytic systems have also been studied as comblike polymers templates for complexation with ionic mesogenes in investigations relevant to pH-responsive systems and artificial biomembranes. 31 Recently, we have reported the use of cationic dendronized polymers as a model system to design comblike liquid-crystalline polymers where microphase-segregated structures can be tailored by both the mesogen type and length as well as the generation of the dendronized polymer.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, other types of macromolecular polyelectrolytes have been explored such as dendrimers [11,12] and dendronized polymers, [13,14] leading to richer polymorphism compared to previous systems. In particular it has been shown that for these classes of highly branched systems can form columnar phases of various lattices such as rectangular hexagonal and lamellar types.…”
Section: Introductionmentioning
confidence: 99%